Using sound - Morgan, Sally, 1957-; Morgan, Adrian (New York : Facts on File, 1994)
Examines the links between design in the natural world and design in modern technology through an investigation of the basic principles of sound, and includes simple experiments, definitions of key terms, photographs, and diagrams.
Sound waves -- Making sounds -- Amplification and soundproofing -- Ultrasound and infrasound.
Includes index.
Science Books & Films (A.A.A.S.).
Wilson's Junior High School.
Science Books & Films (A.A.A.S.), April 1995.
Wilson's Junior High School, September 1995.
6.9
Keywords: Sound-waves -- Juvenile literature; Sound -- Juvenile literature; Sound-waves.; Sound; Sound waves; Sound